PARTISIPASI MASYARAKAT DALAM BENTUK PESAN SINGKAT PENDUDUK (PESDUK) DI KOTA CIMAHI - Larasati, Dini (Jurnal Mahasiswa Ilmu Pemerintahan, 2014)
Kota Cimahi is a new administrative region established in 2002. As a new city, the Cimahi government attempt to provide the best public service to people. It is due to the absence of specified complaining media for the people. Furthermore, in the context of regional autonomy, public space and social involvement in the government is highly expected. Due to these reasons, Population Short Message (Pesduk) program is established to bring the government to get closer to the people, in order to carry out the development together. It cannot be separated from the social will and solidarity, both from leader and bureaucracy. In addition, the Cimahi municipal government expects the Pesduk program could increase the community participation through indirect means of communication. The media used are also quite simple and very common among people, through short messages (SMS) and the website. Moreover, for urban people, the use of technology is not new anymore. This study is examined through two perspectives, political communication and participation. The theory of participation aimed to examine the increased community participation in governance through Pesduk program. The quite simple mechanism ofPesdukprogram is analyzed through the theory of political communication. Therefore, Pesduk mechanism involves two parties, by which people make a complaint and the government responds. Indirect communication occurs, but it is perceived by the user and the provider. The process of data collection is conducted by interview and literary study. Through simple mechanism of Pesduk, people can communicate directly with the government without any representative or conventional mechanisms.Â Pesdukis also shown to be effective in improving community participation to build the Cimahi City.However, Pesdukis still need for improvement because there still many deficiencies to be corrected, such as regulatory, resource, and service standards. Key Words:Cimahi City, PesanSingkatPenduduk, Participation, and Political Communication.